Emotional care experienced by hospitalised patients: development and testing of a measurement instrument - Williams, Anne; Kristjanson, Linda (Blackwell Publishing, 2008)
Aims and Objectives: This paper describes the development and preliminary psychometric testing of an instrument that evaluates the emotional care experienced by patients during hospitalisation.Background: Previous qualitative work using the Grounded Theory method identified the characteristics of interpersonal interactions that hospitalised patients perceived to be therapeutic. Three conditions were associated with the patient's experience of emotional comfort: the patient's perceived Level of Security, Level of Knowing and Level of Personal Value. Questions relating to each of these conditions were included in this new instrument.Design: Instrument development and psychometric testing.Method: Preliminary psychometric testing was carried out in four phases: construction of the instrument; assessment of face and content validity; testing for clarity and feasibility for use with hospitalised patients; assessment of reliability, construct validity of the tool and assessment of the internal structure.Conclusion: A hospital-wide survey was carried out and the instrument was completed by a total sample of 132 patients. Two of the three sub-scales achieved an internal consistency estimate of at least 0.70. The construct validity of the tool confirmed the previously identified characteristics of patients in need of additional emotional care. Exploratory factor analysis established two of the sub-scales and identified a fourth sub-scale which was named "Level of Connection". Encouraging reliability and validity estimates were obtained and the instrument was improved. Further testing with larger samples is recommended. Relevance to clinical practice: This questionnaire, which is completed by hospitalised patients, differs from other instruments because it evaluates the interactions of all hospital staff rather than only nursing staff. This instrument can be used to identify patients who may be in need of additional emotional care and to evaluate the effectiveness of interventions directed at improving the emotional well-being of patients.